Functional Organization of the Brain and Psychic Activity: A View Beyond Luria (With Luria) - Pena-Casanova, J (KnE Life Sciences, 2018)
This paper reviews, elaborates, and rebuilds Luria’s model of the three functional units of the brain. As a result, five functional brain units have been delineated: preferential (unit for life-support and arousal regulation), limbic (unit for valuation/motivation and for context memory), cortical and thalamic-cortical (“the conscious agent”), basal ganglia (”the reinforcer”), and cerebellar (”the supervisor”). The new model is more realistic; it includes elements missing from Luria’s model and avoids a corticocentric approach. It will allow a better analysis of the effects of brain pathology on cognition, neuropsychiatry, and behavior. Within the framework, the concept of complex functional system is maintained and expanded. Keywords: brain, functional model, complex systems, cortex, Luria